Direito de personalidade a autodeterminação da identidade de gênero : limites e possibilidades para sua configuração no direito brasileiro - Dantas, Ana Cecilia de Morais e Silva (2019)
This thesis aims to study the legal treatment reserved for the personality rights of people whose sexualities are dissonant of the binary patern male/female, especially regarding the right to gender identity. Its basic hypothesis is that the naturalization and institutionalization of binary sexual classifications, with the consequent pathologization of divergent identifications, legitimizes violations of the rights of the personality to the body itself and the identity of people whose sexuality escapes these standards. As a secondary hypothesis it holds that the legal admission of alternative (non-binary) sexual identities may prove to be protection against compulsory changes in the bodies and identities of people of divergent sexuality. The thesis adopts queer theory as a theoretical framework able to denature sexual differences and destabilize gender identities, by using the questions formulated by this theory as well as those formulated to its bases. Its development has an epistemological part, configured in the first three chapters, in which basic concepts are worked out concerning the theoretical framework, as well as boundaries concerning personality rights and divergent sexualities. The descriptive part proposes to examine the most relevant decisions taken by the Brazilian Superior Courts on divergent sexualities. The analytical part, however, seeks to present realistic conclusions based on the confrontation of queer theory with legal problems raised by the questioning of the ideas of subject and identity proposed by it, especially to conclude that rather than thinking about alternative gender identities, it may be more useful to the Legal Order to abolish stigmatizing sexual classifications. This research, of basic nature, since it aims to generate knowledge, is especially constructed under the methodology of analysis of the Law from a gender perspective, proposed by Facio, as well as it uses the methodology of decisions analysis, from Freitas Filho and Lima, directed to comparing judicial decisions as well as analyzing the decision-making processes.